2022
DOI: 10.1002/adom.202200332
|View full text |Cite
|
Sign up to set email alerts
|

Photodetector Arrays Based on MBE‐Grown GaSe/Graphene Heterostructure

Abstract: mechanical strength, flexibility, and chemical stability. [1][2][3] However, the absence of a bandgap in graphene has limited its application in optoelectronics. [4] This has introduced a passive way of using graphene by integrating it with other functional materials. [5,6] Integration of graphene with 1D or 2D materials, such as inorganic semiconductors, [7,8] chalcogenides, [9][10][11] and hexagonal boron nitride (h-BN), [12][13][14] has created interesting and tunable optoelectronic properties suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Post-transition metal chalcogenides, including the two-dimensional gallium monochalcogenide (2D-GMC) family, have been becoming a rising star in the field of condensed matter physics and offering opportunities for engineering novel optoelectronic applications in recent years, thanks to possessing unique mechanical, electronic, and optical properties with the large optical window in 2D limit. In particular, noncentrosymmetric ε-phase gallium selenide (GaSe) that is commonly observed in various synthetic methods is one of the potential candidates for electronics, second-harmonic generation, especially for photoelectrochemical and photodetection applications with low dark current, relatively high photoresponsivity, and fast response time. In addition, many researchers have demonstrated that leveraging hybrid dimensionality figure of merits, such as integration of 2D-layered materials with 3D substrates/templates via heteroepitaxy, could be a crucial benefit to enhance the performance of 2D-based optoelectronic devices. In fact, that allows for improving optical absorption efficiency, forming type-II band alignment mixed-dimensional heterostructures, and reducing unintentional contamination during chemical/mechanical exfoliation. , During the past decade, many efforts have been made to fabricate 2D/3D mixed-dimensional heterostructures by either chemical or physical deposition methods.…”
Section: Introductionmentioning
confidence: 99%
“…Post-transition metal chalcogenides, including the two-dimensional gallium monochalcogenide (2D-GMC) family, have been becoming a rising star in the field of condensed matter physics and offering opportunities for engineering novel optoelectronic applications in recent years, thanks to possessing unique mechanical, electronic, and optical properties with the large optical window in 2D limit. In particular, noncentrosymmetric ε-phase gallium selenide (GaSe) that is commonly observed in various synthetic methods is one of the potential candidates for electronics, second-harmonic generation, especially for photoelectrochemical and photodetection applications with low dark current, relatively high photoresponsivity, and fast response time. In addition, many researchers have demonstrated that leveraging hybrid dimensionality figure of merits, such as integration of 2D-layered materials with 3D substrates/templates via heteroepitaxy, could be a crucial benefit to enhance the performance of 2D-based optoelectronic devices. In fact, that allows for improving optical absorption efficiency, forming type-II band alignment mixed-dimensional heterostructures, and reducing unintentional contamination during chemical/mechanical exfoliation. , During the past decade, many efforts have been made to fabricate 2D/3D mixed-dimensional heterostructures by either chemical or physical deposition methods.…”
Section: Introductionmentioning
confidence: 99%
“…Gallium selenide (GaSe) is a compound in the III-VI group that has gained considerable interest recently due to its exceptional properties and potential applications in various fields including photodetectors [1][2][3][4][5][6], water splitting [6][7][8], lasers [9][10][11][12], and nonlinear optics [13][14][15]. GaSe can crystallize in four different polytypes, namely β-, ε-, γ-, and δ-phase structures, which correspond to the space groups P6 3 /mmc (D 4 6h ), P6m2(D 1 3h ), R3m (C 5 3v ), and P6 3 mc (C 4 6v ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, large‐scale array imaging is still a considerable challenge due to the engineering bottlenecks and theoretical limitations. [ 28 ] To name a few, clean transfer of 2D materials and uniform growth of QDs/nanowires are the primary technical bottlenecks to achieve a homogeneous preparation of the array unit. [ 29 ] Meanwhile, a high photoconductive gain is usually at the cost of sacrificing the response time due to the limitation of the defect state.…”
Section: Introductionmentioning
confidence: 99%